Cervical vaporization in LSIL and persistent HPV infection - B. Navarro Santana; R. Sanz Baro; R. Orozco; J. Plaza Arranz (Elsevier, 2018)
Objective: To assess rates of negative cytology and high-risk HPV testing after CO2 laser treatment for low-grade lesions and persistent infection with high-risk HPV as well as factors that can influence these rates. Material and methods: Between February 2011 and January 2015, 124 cervical vaporizations were performed with a CO2 laser in patients presenting persistent infection with high-risk HPV or LSIL of CIN I that had persisted for more than 2 years. Data on parity, condom use, oral contraceptive use, smoking, vaccination against HPV, and immune status were collected and the relationship with rates of negative cytology and high-risk HPV testing was studied. Results: We performed cytology, colposcopic and high-risk HPV detection 6 months after treatment in 116 patients (93%). Seventy-nine percent of patients had benign cytology in this control and 60% had negative results for HPV. Both parameters were normalized in 54% of patients. Mean follow-up was 22.35 months. Rates of negative cytology testing showed no significant relationship with any of the variables studied. Regarding rates of negative high-risk HPV testing, there is a statistically significant relationship with age younger than 45 years; type of high-risk HPV other than 16 and 18; and nulliparity and condom use. Among patients with persistent HPV infection and abnormal cytology at 6 months of vaporization, 55% had normalized cytology results but only 14.7% had negative results for high-risk HPV at the end of follow-up. Conclusions: CO2 laser vaporization is a simple, safe, and successful outpatient treatment that can be performed without anesthesia. Keywords: Cervical Vaporization, VPH, LSIL